The Legal Force of the Cooperation Agreement Letter in a Cooperation Agreement is Reviewed According to Article 1320 of the Civil Code - Irma Shintia Kumaralo; Risdalina Risdalina; Indra Kumala Sari M (International Journal Labs, 2023)
In every activity that is an agreement, of course, there is an agreement that has been made. Whether it is in business, or in certain special matters. This study aims to find out and analyze the regulation of cooperation agreement letters in the civil code (hyperdata). As well as knowing and analyzing the Principles and Determining Factors in Making a Draft Contract (Cooperation Agreement). This research belongs to the normative type of research. So it can be known that agreements are specifically regulated in the Civil Code, Book III, Chapter II on